Electro bioremedation of oil bottoms tank - Pucci, Graciela N. (2013)
The aim of this study was to use a voltage difference to increase the bioavailability of hydrocarbons presents in the bottom sediments of oil tank. This experiment was carried out in a glass cuba with three compartment communicated by phosphate-buffered saline bridges that allowed the voltage difference and maintained the soil pH at optimum values for bacterial life. After several 4 days the bioavailability of hydrocarbon was increased by 18.8% in the area near the anode and 5.5% in the area near the cathode.